2020
DOI: 10.1007/s10915-020-01152-w
|View full text |Cite
|
Sign up to set email alerts
|

Kernel Based High Order “Explicit” Unconditionally Stable Scheme for Nonlinear Degenerate Advection-Diffusion Equations

Abstract: In this paper, we present a novel numerical scheme for solving a class of nonlinear degenerate parabolic equations with non-smooth solutions. The proposed method relies on a special kernel based formulation of the solutions found in our early work on the method of lines transpose and successive convolution. In such a framework, a high order weighted essentially non-oscillatory (WENO) methodology and a nonlinear filter are further employed to avoid spurious oscillations. High order accuracy in time is realized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…where µ = e −α(b−a) . Hence, following the idea in [10], when φ is a periodic function, we can approximate the first derivative φ ± x with (modified) partial sums in (2.11),…”
Section: Periodic Boundary Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…where µ = e −α(b−a) . Hence, following the idea in [10], when φ is a periodic function, we can approximate the first derivative φ ± x with (modified) partial sums in (2.11),…”
Section: Periodic Boundary Conditionsmentioning
confidence: 99%
“…Note that there is an extra term for k = 3. As remarked in [10], such a term is needed for attaining unconditional stability of the scheme. An error estimate for the approximation (2.14) regarding the truncation of the infinite sum, carried out in [10], showed that keeping k terms of the partial sums led to…”
Section: Periodic Boundary Conditionsmentioning
confidence: 99%
See 3 more Smart Citations